(3QSGdI ef ajKGZhQS Edi eJeQO UbdjIs - (3ajKGZhQKs
(3ChdgG (B:s
(3QSGdI ahKGZhQS Edi eJeQO UbdjI aEf GdGWHGA dGjVefhf Cf jeQVhG eY GdeQVi ef JeLjO GdadGSaI SHMGfc jG eHOY Gdcd s
(3BNQgG (B:s
(3hEf cGf Ybdg CcKQ ef COHg jaQZ GdYbd HbOQ RjGOJg aQhYkG JHdZ HUGMHgG GdJeGe hef de jcf dg Ybd hdG GOH cGf NGQLkG Yf Mce GdfGS s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdadSaI hGdefWbs